2021
DOI: 10.1371/journal.pone.0250934
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on short-term prognosis, length of stay, and costs in patients with acute kidney injury: A nationwide survey in China

Abstract: Background International data suggest that people with diabetes mellitus (DM) are at increased risk for worse acute kidney injury (AKI) outcomes; however, the data in China are limited. Therefore, this study aimed to describe the association of DM with short-term prognosis, length of stay, and expenditure in patients with AKI. Methods This study was based on the 2013 nationwide survey in China. According to the 2012 Kidney Disease: Improving Global Outcomes (KDIGO) and expanded criteria of AKI, 7604 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…For example, although the finding that a history of NSAID use and thiazide diuretics were each associated with lower odds of mortality in the univariable mode was unexpected given their associations with AKI [ 24 , 25 ], this association was not apparent in the multivariable model. Similarly, the crude statistically significant association between diabetes and all-cause inpatient mortality was not seen in the multivariable model, which is in keeping with conflicting data in the literature on this association [ 26 , 27 ]. By contrast, advancing CKD stage was associated with reduced all-cause inpatient mortality in the multivariable but not in the univariable model in our study, which is similar to a retrospective study of 82,711 hospitalized AKI events from the United States Department of Veterans Affairs healthcare system by Lafrance and Miller.…”
Section: Discussionsupporting
confidence: 80%
“…For example, although the finding that a history of NSAID use and thiazide diuretics were each associated with lower odds of mortality in the univariable mode was unexpected given their associations with AKI [ 24 , 25 ], this association was not apparent in the multivariable model. Similarly, the crude statistically significant association between diabetes and all-cause inpatient mortality was not seen in the multivariable model, which is in keeping with conflicting data in the literature on this association [ 26 , 27 ]. By contrast, advancing CKD stage was associated with reduced all-cause inpatient mortality in the multivariable but not in the univariable model in our study, which is similar to a retrospective study of 82,711 hospitalized AKI events from the United States Department of Veterans Affairs healthcare system by Lafrance and Miller.…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have shown that diabetes is an important risk factor for CSA-AKI [4,18,19], but there are few studies on the effect of diabetes on the adverse prognosis of CSA-AKI. Tan's study pointed out that diabetes was not associated with the failure of renal function recovery after AKI [20], but this study only included patients with AKI caused by various etiologies, and the conclusion was insufficient guidance for AKI caused by special etiology. Our results indicated that preoperative diabetes is an independent factor resulting in poor renal function recovery in patients with CKD after CSA-AKI.…”
Section: Discussionmentioning
confidence: 95%
“…In China, a country with a large DM patient population, a national survey indicated that diabetic status was positively associated with the length of stay and hospital expenditure after adjusting for possible confounders 53 . In comparison, in fast‐growing economies, such as Ethiopia, 19.76% (95% CI; 16.2–23.8) of the study population (420 DM patients) developed AKI, with a median follow‐up period of 30.75 months 40 .…”
Section: The Global Atlas Of Aki In Dm: Mapping the Way Forward In Ad...mentioning
confidence: 99%